Diastereoselective anomeric oxygen to carbon rearrangements of silyl enol ether derivatives of lactols. - Dixon, D; Ley, S; Tate, E (1998)
Lewis acid promoted oxygen to carbon rearrangement of anomerically linked silyl enol ethers gives a new and diastereoselective route to the corresponding 2-α-hydroxyketone substituted products.